PLAC8 attenuates pulmonary fibrosis and inhibits apoptosis of alveolar epithelial cells via facilitating autophagy - Wei Sun; Bo Zhao; Zhong He; Lihua Chang; Wei Song; Yingying Chen (Communications Biology)
Abstract Idiopathic pulmonary fibrosis (IPF) is an irreversible lung condition that progresses over time, which ultimately results in respiratory failure and mortality. In this study, we found that PLAC8 was downregulated in the lungs of IPF patients based on GEO data, in bleomycin (BLM)-induced lungs of mice, and in primary murine alveolar epithelial type II (pmATII) cells and human lung epithelial cell A549 cells. Overexpression of PLAC8 facilitated autophagy and inhibited apoptosis of pmATII cells and A549 cells in vitro. Moreover, inhibition of autophagy or overexpression of p53 partially abolished the effects of PLAC8 on cell apoptosis. ATII cell-specific overexpression of PLAC8 alleviated BLM-induced pulmonary fibrosis in mice. Mechanistically, PLAC8 interacts with VCP-UFD1-NPLOC4 complex to promote p53 degradation and facilitate autophagy, resulting in inhibiting apoptosis of alveolar epithelial cells and attenuating pulmonary fibrosis. In summary, these findings indicate that PLAC8 may be a key target for therapeutic interventions in pulmonary fibrosis.